An Introduction to Computational Methods - Redish, K. A. (London : English Universities Press, 1961)
Applied mathematics is expanding at a great rate, and every year mathematical techniques are being applied in new fields of physical, biological and economic sciences. This series aims at keeping abreast of these developments. Additionally, the object of this series is to provide texts in applied mathematics which will cover school and university requirements. The texts are convenient for use by pure and applied mathematicians and also by scientists and engineers wishing to acquire mathematical techniques to improve their knowledge of their own subjects.
Bibliography p. [210]-212.
ne 8/03/2018
Loan
Keywords: Numerical Calculations; Algebra; Mathematics